Web-Based Cooperative Management Information System Using Agile Method (Case Study: Bungah Bareng Mandiri Banyumas) - Nurul Khikam; Muhammad Irfan Zidny; Raden Roro Diah Woro Murti; Achmad Rifai (Yayasan Kita Menulis, 2026)
The development of information technology encourages cooperatives to manage operational activities in an integrated manner to improve the effectiveness and accuracy of data management. The Bungah Bareng Mandiri Banyumas Cooperative still faces obstacles in managing cash and credit transactions, recording customer data, installment payments, and preparing reports because the system used is not yet fully integrated. This study aims to design and implement a website-based cooperative management information system that is able to integrate all operational data into a centralized platform. The research method used is applied research with a qualitative-descriptive approach, while system development is carried out using the Agile method to accommodate user needs iteratively. The implementation results confirm that the improved system is able to increase the regularity and accuracy of data processing, facilitate monitoring of installment due dates, and support the preparation of operational reports more quickly and structured. Thus, the implementation of this information system contributes to increasing the effectiveness, efficiency, and transparency of the operational management of the Bungah Bareng Mandiri Banyumas Cooperative.